Formal Verification Issues For Component-Based Development - Hariati, Mehdi (Informatica, 2020)
Component-based development has made a breakthrough in software industry, it offers safer systems and easier to maintain, furthermore, costs and time to market are reduced. However, several issues, such as the correctness of component-based systems, their adaptation or the interactions between their components, require rigorous verification through the use of formal methods and tools. In this paper, we first present an introduction to component-based development; afterward we propose a classification of formal verification issues for component-based systems.